2014
DOI: 10.2174/13894501113149990194
|View full text |Cite
|
Sign up to set email alerts
|

MDM2-p53 Interaction in Paediatric Solid Tumours: Preclinical Rationale, Biomarkers and Resistance

Abstract: p53 is one of the main regulators of apoptosis, senescence, cell cycle arrest and DNA repair. The expression, function and stabilization of p53 are governed by a complex network of regulators including p14(ARF) and MDM2. MDM2 is the main negative regulator of p53 activity and stability. Unlike tumours in adults, which tend to overcome p53 regulation by p53 mutations, the paediatric tumours neuroblastoma and sarcoma frequently retain wild type p53. Nevertheless, in childhood cancer the p53 pathway is commonly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 102 publications
0
34
0
Order By: Relevance
“…The Mdm2-p53 interaction in sarcomas has recently received attention on account of a new therapeutic approach targeting this interaction[10,11,16]. MDM2 amplification/overexpression is characteristic of well-differentiated/dedifferentiated liposarcomas (DDLS), but is also identified in a small percentage of other sarcomas[17,18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Mdm2-p53 interaction in sarcomas has recently received attention on account of a new therapeutic approach targeting this interaction[10,11,16]. MDM2 amplification/overexpression is characteristic of well-differentiated/dedifferentiated liposarcomas (DDLS), but is also identified in a small percentage of other sarcomas[17,18].…”
Section: Discussionmentioning
confidence: 99%
“…RMSs are aggressive pediatric tumors, and there have been recent preclinical trials of Mdm2 inhibitors in RMS[10,11]. Radiation-induced RMS has rarely been described, mostly among Chinese patients treated for nasopharyngeal cancer[8,9,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of Wip1 in neuroblastoma may repress p53 function by two signaling pathways, one is the Wip1-p53 pathway, and the other is the Wip1-Mdm2-p53 pathway (35), resulting in tumorigenesis. In addition, a previous report demonstrated that Wip1 was significantly overexpressed in 56% of cancer tissues, and promoted tumor progression to a higher stage, poor prognosis and chemotherapy resistance (Table I) (32).…”
Section: Wip1 In Neuroblastomamentioning
confidence: 99%
“…A recent patent utilizing certain small molecule compounds prevents p53 downregulation by inhibiting its interaction with the MDM2 protein [29]. MDM2 is a known suppressor of p53, and by selectively inhibiting its ability to function, the patent aims to restore normal p53 function [30]. …”
Section: Squamous Cell Carcinoma In Patients With Debmentioning
confidence: 99%